2022
DOI: 10.1038/s41598-022-21576-8
|View full text |Cite
|
Sign up to set email alerts
|

Different antibody-associated autoimmune diseases have distinct patterns of T follicular cell dysregulation

Abstract: Autoantibodies are produced within germinal centers (GC), in a process regulated by interactions between B, T follicular helper (Tfh), and T follicular regulatory (Tfr) cells. The GC dysregulation in human autoimmunity has been inferred from circulating cells, albeit with conflicting results due to diverse experimental approaches. We applied a consistent approach to compare circulating Tfr and Tfh subsets in patients with different autoimmune diseases. We recruited 97 participants, including 72 patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“… 46 58 59 Furthermore, lower levels of PD1+Tfh cells, PD1+ICOS+Tfh cells and Tph cells were found in JIA patients when compared with controls. Although the frequencies observed of Tfh and Tph cells are not consistent among distinct immune-mediated diseases, 60 some studies described an increased frequency of these T cell subpopulations in peripheral blood and synovial fluid from JIA patients. 48–50 In particular, it was observed that Tph cells are enriched in the joints of oligo JIA patients and in the synovial fluid of ANA+ JIA patients, where they express many B cell helper-associated markers and have the capacity to induce B cell differentiation and antibody production.…”
Section: Discussionmentioning
confidence: 87%
“… 46 58 59 Furthermore, lower levels of PD1+Tfh cells, PD1+ICOS+Tfh cells and Tph cells were found in JIA patients when compared with controls. Although the frequencies observed of Tfh and Tph cells are not consistent among distinct immune-mediated diseases, 60 some studies described an increased frequency of these T cell subpopulations in peripheral blood and synovial fluid from JIA patients. 48–50 In particular, it was observed that Tph cells are enriched in the joints of oligo JIA patients and in the synovial fluid of ANA+ JIA patients, where they express many B cell helper-associated markers and have the capacity to induce B cell differentiation and antibody production.…”
Section: Discussionmentioning
confidence: 87%
“…In another study, Ribeiro et al reported that the frequency of circulating Tfh and Tfr cells was decreased in patients with RA and that the Tfr/Tfh ratio was similar to HCs (Ribeiro et al, 2022). These results show inconsistent results on the role of the Tfr/Tfh ratio in the pathogenesis of RA.…”
Section: Gut Microbiota Can Modulate the Tfh/tfr Balancementioning
confidence: 96%
“…B cells produce antibodies against extracellular pathogens and toxins. Antibodies are produced within germinal centers, regulated by interactions between B, Tfh, and Tfr cells (Ribeiro et al, 2022). Tfh cells are a CD4 T cell lineage that interacts with B cells to form germinal centers, promote differentiation into plasma cells, promote class-switching, somatic hypermutation, and the generation of high-affinity antigen-specific memory B cells and antibody-producing cells (Diamanti et al, 2016;Wang et al, 2019b;Zeng et al, 2022).…”
Section: Gut Microbiota Can Modulate the Tfh/tfr Balancementioning
confidence: 99%
“…The absence of CXCR5 leads them to exit germinal centers and position themselves within inflamed tissues by expressing other chemokine receptors such as CCR2 and CCR5, where Tph cells induce B cell differentiation through the production of IL-21 [14]. Increased numbers of Tph cells have also been observed in SLE (59)(60)(61)(62), RA [58][59][60][61], and pSS [54,67,68].…”
Section: Pd-1/pd-l1/pd-l2 In Central and Peripheral Tolerancementioning
confidence: 99%